Proyecto de inversión de una hacienda productora de banano orgánico en Balao provincia del Guayas - Vega Rodríguez, Sara Raquel (2019)
Currently, banana production is one of the main sources of income for producers in the Balao canton, as well as for many families working in this agricultural sector. It should be noted that banana exports are one of the main non-oil revenues that the country has within the General Budget of the State. Currently organic production is being an option to not lose biodiversity, and in foreign markets is increasing the level of consumption by not using chemicals in them and thus also take care of the health of human beings….